Evaluation Of The Performance Of Selfmix Feed-Based Layer Production Using And Not Using Feed Additive In Ponggok Village, Ponggok District, Blitar Regency - Amin, Muhamad Iza Dzul Fikar; M.P, Lestariningsih; Khopsoh, Binti (UNIVERSITAS ISLAM LAMONGAN, 2025)
This research was conducted in Ponggok Village, Ponggok District, Blitar Regency. The purpose of this study is to determine feed consumption, egg production, and physical quality of eggs based on self-mixed feed, using and not using additive feed. The data collection technique uses a qualitative approach with observation, interview, and documentation methods. The data analysis technique uses a descriptive analysis method. The study results show that the average age of farmers is 45-60 years old. The average level of elementary education. The average chicken strain used by farmers is the malindo strain with an average population of 3000-6000 heads. Production appearance includes feed consumption, hen day production (HDP), egg weight, shell color, shell texture in chickens aged 24, 25, and 26 weeks. The average level of feed consumption without the addition of feed additives was 120.6 grams, while feed consumption with feed additive added was 120 grams. The average HDP without the addition of feed additives to feed is 86 %, while HDP with the addition of feed additive to feed is 90.6%. The average weight of eggs without the addition of feed additives in feed was 55.8 grams (medium level), while the weight of eggs with the addition of feed additives in feed was 62.72 grams (extra level). The average color of egg shells without the addition of feed additives to feed is at level 7 (Mahogany), while the color of egg shells with the addition of feed additives to feed is at level 9 (Camel). The average texture of egg shells without the addition of feed additives to feed is at level 3 (slightly coarse), while the texture of shells with the addition of feed additives to feed is at level 1 (smooth).